Quality of comply boards from the industrial waste of palm and bamboo - Ningsih, Rima Vera; Lestari, Dini; Wulandari, Febriana Tri; Valentino, Niechi; Fahrussiam, Fauzan; Prasetyo, Andrie Ridzki (Jurnal Biologi Tropis, 2024)
Requisite of boards as a material for furniture is increasing. Therefore, alternative materials are needed to replace wooden boards such as comply boards. This study aims to determine the quality of comply board from palm and bamboo waste using PVAc adhesives. The treatment used is 12% and 14% adhesive percentages. Parameter tests of comply board of physical properties include moisture content, density, and thickness development; mechanical properties include modulus of elasticity (MOE) and modulus of rupture (MOR). The mechanical properties of adhesive content have a significant effect on the mechanical properties of comply board palm and bamboo namely MOE and MOR the Physical Properties of the resulting comply board meet SNI 03-2105-2006 standards, namely for the parameters of Water Content, Density, Water Absorption. The mechanical properties of comply boards, namely Modulus of fracture (MoR) are not included in these standards. The condition of the results of this study is thought to be.